Slavery, philosophy, and American literature, 1830-1860 - Lee, Maurice S. (Cambridge studies in American literature and culture, 2005)
Maurice Lee demonstrates how the slavery crisis became a crisis of philosophy. Authors including Poe, Stowe, Douglass, Melville, and Emerson tried - and failed - to find rational solutions to the slavery conflict. Drawing on antebellum moral philosophy, political theory, and metaphysics, Lee brings a fresh perspective to the literature of slavery.